Re-examining locus standi of non-state entities and individuals under the African Regional Economic Communities and the African Continental Free Trade Area - Oluyeju, Femi (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.